2016
DOI: 10.56829/2158-396x.16.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous Assumptions and Unspoken Limitations: A Disability Studies in Education Response to Morgan, Farkas, Hillemeier, Mattison, Maczuga, Li, and Cook (2015)

Abstract: In this article, we critically review the work of Morgan et al. (2015) and offer Disability Studies in Education (DSE) as an alternative conceptualization to traditional research within special education. We first unpack many of Morgan et al.'s (2015) assumptions, which are grounded in deficit discourses about children, family structures, economic status, and home cultures. Next, we identify flaws in their research design and methodology. Finally, we elaborate on how, through naming and making visible the work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although interactional with "subjective experience," a disability cannot be construed as purely socially constructed. Some DS advocates seem to abjure identification of children as actually having disabilities and judge special education to be deficit-focused and segregationist, and they accuse special education of having eugenic implications (e.g., Collins et al, 2016;Connor, 2020). These DS advocates, somewhat erroneously, speak only of bodily inclusion, ignoring other important aspects of learning (Hornby & Kauffman, 2021;Kauffman & Hornby, 2020).…”
Section: The Era Of Inclusionmentioning
confidence: 99%
“…Although interactional with "subjective experience," a disability cannot be construed as purely socially constructed. Some DS advocates seem to abjure identification of children as actually having disabilities and judge special education to be deficit-focused and segregationist, and they accuse special education of having eugenic implications (e.g., Collins et al, 2016;Connor, 2020). These DS advocates, somewhat erroneously, speak only of bodily inclusion, ignoring other important aspects of learning (Hornby & Kauffman, 2021;Kauffman & Hornby, 2020).…”
Section: The Era Of Inclusionmentioning
confidence: 99%
“…The multidisciplinary field of Disability Studies (DS) does just that and has many insights to offer. However, there is a continued divide between knowledge from DS and other scholarly fields which upholds certain marginalization principles by using disability to argue against equality and by justifying the marginalization of all minority groups (e.g., Baynton, 2001;Collins et al, 2016). Even now, overrepresentation of different marginalized groups in referrals to 'special education' systems implies that disability serves as an over-all exclusionary mechanism; differences get labelled as deficient and on this basis students of marginalized groups are disproportionally excluded from mainstream education (e.g., Collins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a continued divide between knowledge from DS and other scholarly fields which upholds certain marginalization principles by using disability to argue against equality and by justifying the marginalization of all minority groups (e.g., Baynton, 2001;Collins et al, 2016). Even now, overrepresentation of different marginalized groups in referrals to 'special education' systems implies that disability serves as an over-all exclusionary mechanism; differences get labelled as deficient and on this basis students of marginalized groups are disproportionally excluded from mainstream education (e.g., Collins et al, 2016). As the importance of a disability lens for the process of inclusive education is often under-estimated, this paper presents empirical examples to illustrate how the lack thereof has a tangible negative impact on disabled students' lives.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have found that students of color are more likely to be identified with disabilities than other students (Cruz et al, 2021; Skiba et al, 2008), particularly in more subjective disability categories such as emotional disturbances (Bal et al, 2019; Donovan & Cross, 2002). Other scholars have found that Black students may be under-identified for some disability categories when predictors like test scores or economic and health indicators are taken into account (Elder et al, 2021; Hibel et al, 2010; Morgan et al, 2015), though these conclusions have received significant pushback (Collins et al, 2016; Skiba et al, 2016). While there are ongoing debates as to which comparisons are most appropriate to understand representation in special education (Ahram et al, 2021; Cruz & Rodl, 2018), it is useful from a policy perspective to distinguish factors that contribute to special education identification.…”
mentioning
confidence: 99%